167k views
5 votes
If f(x) = -3x - 5 and g(x) = 4x - 2, find (f - 9(x).

A. (f- g)(x) = -7x + 3
B. (- 9)(x) = x - 7
C. (f- g)(x) = -7x - 3
D. (f - g)(x) = x - 3

1 Answer

0 votes

Answer:

brutal it rt nh you up to be

Explanation:

have a great day of school and I have a great day of school and I have a great day of school and I have a great day of school and I have a great day☀ of school and I have a great day of school up ur r the United up to be a great day of

User David Bentley
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.